Randomised, Double-blind, Comparative Clinical Study of New Ranibizumab Biosimilar in Neovascular (Wet) Age-Related Macular Degeneration - Apsangikar P (Dove Medical Press, 2021)
Prasad Apsangikar, Pravin Ghadge, Manoj Naik, Santosh Nair, Ravikiran Payghan Reliance Life Sciences Pvt. Ltd, Mumbai, IndiaCorrespondence: Prasad ApsangikarReliance Life Sciences Pvt. Ltd., 282 MIDC, Thane Belapur Road, Rabale, Navi Mumbai, 400701 Tel +919867610090Fax +912235338099Email prasad.apsangikar@relbio.comPurpose: The study was undertaken for regulatory purposes to establish clinical biosimilarity and interchangeability of a ranibizumab biosimilar with reference product.Patients and Methods: A total of 159 subjects with neovascular (wet) age-related macular degeneration (AMD) were dosed with ranibizumab. Initial double blind period of 16 weeks was followed by open-label phase till week 24. Efficacy assessment was performed at weeks 1, 4, 8, 12, 16, 20 and 24 based on best corrected visual acuity. Change in central macular thickness was assessed by optical coherence tomography from baseline to week 24. Immunogenicity assessment was done in both arms at baseline, week 16 and week 24. Safety evaluation included clinical and ophthalmic examination, adverse events, vital signs, laboratory parameters and immunogenicity in both treatment arms.Results: In the biosimilar test arm, 104 (98.11%) and 105 (99.06%) patients lost fewer than 15 letters in visual acuity at week 16 and week 24, respectively, compared with 53 (100%) at both follow-ups in reference arm. In the test arm, 27 (25.47%) and 34 (32.08%) patients gained at least 15 letters in visual acuity till week 16 and week 24 respectively, compared with 17 (32.08%) and 23 (43.30%) in the reference arm. In the test arm, mean change in central macular thickness at 24 weeks was − 89.93 μm against − 64.42 μm in the reference arm. Difference was statistically not significant for any endpoint at 16 and 24 weeks for the primary and secondary endpoints.Conclusion: The evaluation of efficacy, safety and immunogenicity was concluded to show no meaningful clinical difference for biosimilar ranibizumab with the reference product.Keywords: ranibizumab, biosimilar, AMD, intravitreal, visual acuity